2022
DOI: 10.1007/s10567-022-00409-0
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Therapeutic Process Factors in Mental Health Treatment for Autistic Youth

Abstract: Understanding the role of therapeutic process factors in treatment change may prove useful for discerning why some autistic youth benefit from psychosocial interventions that target emotional and psychological aspects of mental health, while others do not. The aim of the current study was to synthesize what is currently known about therapeutic process factors in mental health treatment of emotional and psychological challenges for autistic youth, regarding how process factors have been measured in past researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…While a significant proportion of SSGT studies have reported programme adherence and satisfaction [7], the data of these studies were descriptive. In other words, they did not systematically examine these process factors about outcomes [20].…”
Section: Among Interventions For Verbal and Cognitively Capable Schoo...mentioning
confidence: 99%
See 4 more Smart Citations
“…While a significant proportion of SSGT studies have reported programme adherence and satisfaction [7], the data of these studies were descriptive. In other words, they did not systematically examine these process factors about outcomes [20].…”
Section: Among Interventions For Verbal and Cognitively Capable Schoo...mentioning
confidence: 99%
“…Another discernible limitation in the past SSGT studies was the sparseness of the investigations in common process factors [20]. While a significant proportion of SSGT studies have reported programme adherence and satisfaction [7], the data of these studies were descriptive.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations